Atriplex nummularia LINDL (saltbush) irrigation using desalinator wastewater. - Furtado, Fernando Nobre (2009)
This work aimed to study the advantage of desalinator rejects, by reverse osmoses, in the irrigation of Atriplex nummularia Lindl, known under the name of saltbush and classified as a foddering grass. The experimental sketching was quite given rise to, with four treatment proceedings and three repetitions. The defined ones were: T1, natural soil, irrigated with desalinization's brine; T2, soil with organic manure, irrigated with desalinization's brine; T3, natural soil irrigated with well's water; T4, soil with organic manure, irrigated with well's water. The brine presented CE of 5660 ?S/cm and the well's water, by its turn, CE of 1032 ?S/cm. The productivity in the irrigated treatment with desalinization's brine was upper than that obtained in the other treatments, with the value of 25.000 kg/ha of fresh material, and was statistically different, at the level of 5% fron the irrigated treatment only, with well's water and the use of organic manure, which obtained 14.250 kg/ha. Making the mass balance of the chemical sodim element, the irrigation woul provoke an increasing in sodium's grade, in the soil, of 885 mg/dm3; as only occurred an increasing of 268 mg/dm3, we got the conclusion the plant took 69,7% off from the the thrown out sodium.